2022
DOI: 10.3390/jcm11041047
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Left Atrial Tachycardia following Catheter Ablation of Atrial Fibrillation: 12-Month Success Rates

Abstract: The treatment of atrial tachycardia following catheter ablation of atrial fibrillation is often challenging. Electrophysiological studies using high-resolution 3D mapping systems have contributed significantly to their understanding, and new ablation approaches have shown high rates of acute terminations with low recurrences for the clinical AT. However, patient populations are very heterogeneous, and long-term data of the freedom from any atrial tachycardia or any arrhythmia are still sparse. To evaluate long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“… 1177–1180 Despite pertinent challenges in ablation of AT after AF ablation (difficulty in achieving transmurality, epicardial-dependent tachycardias, and safety concerns in specific areas), recent studies have shown very promising results in acute AT termination and long-term SR maintenance. 1181 , 1182 …”
Section: Postprocedural Managementmentioning
confidence: 99%
“… 1177–1180 Despite pertinent challenges in ablation of AT after AF ablation (difficulty in achieving transmurality, epicardial-dependent tachycardias, and safety concerns in specific areas), recent studies have shown very promising results in acute AT termination and long-term SR maintenance. 1181 , 1182 …”
Section: Postprocedural Managementmentioning
confidence: 99%